La ritualidad en la recuperación de la salud de las familias de la parroquia Bellavista, cantón Espíndola, ruta del Qhapaq-Ñan - Patiño Medina, Cecibel María (2019)
Rituality is a practice that has been exercised since ancient times, several people consider it an alternative to cure their ailments because they find it less expensive and more effective, however the different advances in medicine are causing it to be lost, this research has The objective is to describe the rituals used for the recovery of the health of the families that live in the Bellavista parish, Espíndola canton, route of the Qhapaq-Ñan. It is a descriptive study, with a quantitative and quantitative approach, the method used to collect the information was surveys applied to the heads of family of the Bellavista parish and interviews directed to the Traditional Agents of Health. The sample was made up of 66 families. The results obtained from this research were that the sex of the head of the household is 61% male, which is in an age range between 41-50 years of which 42 % has the complete primary schooling; the predominant productive activity is own farming in 71%; Among the types of rituals that they use for the recovery of health are clean, puffs and sobados, using spoon, egg and medicinal plants as elements; The main diseases of cultural affiliation are bad air 29%, horror 19%, the evil eye 13% and empacho10%. Concluding that the families of the Bellavista parish make use of rituality for the recovery of health. Keywords: ancestral knowledge, traditional health agent, cultural affiliation diseases